Untargeted LC–HRMS profiling followed by targeted fractionation to discover new taste-active compounds in spirits. (15th October 2021) - Winstel, Delphine; Bahammou, Delphine; Albertin, Warren; Waffo-Téguo, Pierre; Marchal, Axel
Graphical abstract: Highlights: New methodology to discover taste-active compounds. Untargeted metabolomic profiling of 48 cognacs. Isolation and characterization of one sweet-tasting compound. First identification of Alc-diHDDC in oak wood and spirits. Abstract: Taste is a key driver of food and beverage acceptability due to its role in consumers' pleasure. The great interest that natural food and beverages now arouse lies notably in the complexity of their taste, which in turn is related to a wide range of taste-active compounds. Going beyond the classic divide between targeted and untargeted strategies, an integrative methodology to spirits was applied. Untargeted profiling of several cognac spirits was implemented by LC–HRMS to identify compounds of interest among hundreds of ions. A targeted fractionation protocol was then developed. By using HRMS and NMR, dihydrodehydrodiconiferyl alcohol was identified and described for the first time in spirits and oak wood. It was characterized as sweet at 2 mg/L in two matrices and was quantified in spirits up to 4 mg/L. These findings demonstrated how this methodology is relevant and effective to discover new taste-active compounds.